MiRNA profiling of biliary intraepithelial neoplasia reveals stepwise tumorigenesis in distal cholangiocarcinoma via the miR-451a/ATF2 axis - Löffler, Moritz; Hu, Jun; Kirchner, Martina; Wei, Xiyang; Xiao, Yi; Albrecht, Thomas; Torre, Carolina de la; Sticht, Carsten; Banales, Jesus M.; Vogel, Monika Nadja; Pathil-Warth, Anita; Mehrabi, Arianeb; et al. (The journal of pathology, 2020)
Distal cholangiocarcinoma (dCCA) is a biliary tract cancer with a dismal prognosis and is often preceded by biliary intraepithelial neoplasia (BilIN), representing the most common biliary non-invasive precursor lesion.